1967
DOI: 10.1126/science.158.3801.635
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of the Moon at the Surveyor V Landing Site

Abstract: The chemical composition of the lunar surface material at a maria landing site has been determined by the alpha-scattering technique. Oxygen, silicon, and aluminum have been identified in the preliminary evaluation of the data. The general chemical composition is similar to that of a silicate of a basaltic type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Table 1 shows a typical Uncertainty Budget for this analysis which includes a number of secondary effects as well as effects of spectral distortion. Counting statistics (A 1 & A 2 ) should not dominate these types of measurements, and we list ten other effects (A 3-6 & B [1][2][3][4][5][6] ) most of which are not usually considered when estimating experimental uncertainties in measurements of this type. We discuss these in turn :-…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows a typical Uncertainty Budget for this analysis which includes a number of secondary effects as well as effects of spectral distortion. Counting statistics (A 1 & A 2 ) should not dominate these types of measurements, and we list ten other effects (A 3-6 & B [1][2][3][4][5][6] ) most of which are not usually considered when estimating experimental uncertainties in measurements of this type. We discuss these in turn :-…”
Section: Methodsmentioning
confidence: 99%
“…See text for discussion of A i and B i . The reduced uncertainty (U 5 ; this is the measurement precision shown in Figure 2) for a given beam is given by U 4 less the systematic contributions (B 3-6 & A [5][6] ) in quadrature. The error bars are given as the "reduced uncertainty" (U 5 , k=1; see Table 1).…”
Section: Tablesmentioning
confidence: 99%
“…The structure of thin films involving polymer blends also have many important applications, and the mixing profiles can be systematically followed by deuterating one polymer and profiling the deuterium by 3 He-NRA [28]. Alternatively, a deuterium primary beam can be used to simultaneously profile specific isotopes using NRA, for example 12 PIXE analyses typically use a 3 MeV proton microbeam : elastic backscattering cross-sections are non-Rutherford for 2 MeV protons on all targets of mass up to at least Fe. This is one good reason why historically PIXE and RBS/EBS spectra were usually analysed completely separately: the ESS spectra, involving complicated and poorly-known cross-sections, were considered practically intractable in general by the PIXE community.…”
Section: Iba Methods and Perspectivesmentioning
confidence: 99%
“…Claims for a 1% accuracy for RBS have often been made -a notable early example is the report by Turkovich et al on the analysis of moon rocks by Surveyor V in 1967 [12] -but these claims have never been supported by a critical analysis of the uncertainty budget: indeed, uncertainty budgets are still not widely used in IBA [1]. Here we will critically review previous RBS work applicable to the determination of the quantity of material in thin films at a high traceable accuracy, and also critically review the methods required to apply RBS traceably at this accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration by Turkevich et al (12) that the surface regions of the moon were highly differentiated, and the subsequent confirmations of these results by the analyses of samples from the Apollo 11 and Apollo 12 missions, showed that both titaniferous basalt and anorthosite were present on the lunar surface; thus, a modification of previous ideas in regard to lunar structure was required. A model of a melted surface layer and a cool interior for the early structure of the moon was adopted (13).…”
mentioning
confidence: 98%